2021
DOI: 10.1002/pol.20210481
|View full text |Cite
|
Sign up to set email alerts
|

β‐Cyclodextrin‐based macroporous monoliths: One‐pot oil‐in‐oil emulsion templating and adsorption

Abstract: The ability of β‐cyclodextrin (β‐CD) to form a host–guest complex with relatively hydrophobic molecules such as bisphenol A (BPA), a common wastewater contaminant, has inspired the development of β‐CD‐containing polymers for adsorption applications. For the most part, these polymers are powders, which can limit their applicability. Here, low‐density (~0.1 g cm−3), macroporous monoliths based on unmodified β‐CD were synthesized using emulsion templating. The relatively simple, one‐pot, polyurethane synthesis to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Their unique structure allows molecular flow, such as that occurring in biomolecules, to be facilitated by the macroporous structure, whereas the mesoporous structure, having a larger surface area, leads to greater mass transportation . This makes them highly efficient functional materials for a wide range of applications, including highly efficient separation, ion exchange, catalysis, photocatalysis, adsorption, energy conversion and storage, as well as biomedicine . Several methods have been reported to fabricate polymer monoliths, including cross-linking, free radical polymerization, and thin-layer membrane fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…Their unique structure allows molecular flow, such as that occurring in biomolecules, to be facilitated by the macroporous structure, whereas the mesoporous structure, having a larger surface area, leads to greater mass transportation . This makes them highly efficient functional materials for a wide range of applications, including highly efficient separation, ion exchange, catalysis, photocatalysis, adsorption, energy conversion and storage, as well as biomedicine . Several methods have been reported to fabricate polymer monoliths, including cross-linking, free radical polymerization, and thin-layer membrane fabrication .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these, the effect of macroporous structure of polymers on BPA removal has been also investigated. In this respect, high internal phase emulsion (HIPE) templating, which is one of the most common routes for creating hierarchical macroporosity, was used to synthesize inorganic (Kovačič et al, 2014) and organic foams (Berezovska et al, 2022). HIPEs are concentrated emulsions defined with internal phase volume fractions higher than 0.74 (Mert & Mert, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…HIPEs are concentrated emulsions defined with internal phase volume fractions higher than 0.74 (Mert & Mert, 2022). When a HIPE is used to generate a foam via polymerization, resulting macroporous foam is a polyHIPE (Berezovska et al, 2022; Mert & Mert, 2021, 2022). PolyHIPE‐derived macroporous ZnO foams were tested in BPA degradation by Kovačič et al, and it was demonstrated that the foam exhibited 38% of total organic carbon removal (Kovačič et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…28−32 To date, porous clay, 33 mineralbased materials, 14 metallic foams, 34 porous carbon, 35 and porous polymers 36,37 are the most commonly used framework materials for shape-stabilized PCM. High internal phase emulsion templated polymers (PHP) as porous polymers have been used in a wide variety of applications such as adsorption, 38,39 purification, 40,41 separation, 42 controlled release, 43,44 and scaffolding, 45 and there is limited research in energy storage application. 46,47 Recently, porous PHP foams have begun to gain attention for the stabilization of PCMs owing to their superior features such as shape stabilization, enclosure ability, high loading rate, excellent structural stability, and interpenetrating pore morphology.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, in addition to PCM microcapsules, the application of shape-stable porous materials as a PCM carrier has received great interest in the literature. To date, porous clay, mineral-based materials, metallic foams, porous carbon, and porous polymers , are the most commonly used framework materials for shape-stabilized PCM. High internal phase emulsion templated polymers (PHP) as porous polymers have been used in a wide variety of applications such as adsorption, , purification, , separation, controlled release, , and scaffolding, and there is limited research in energy storage application. , Recently, porous PHP foams have begun to gain attention for the stabilization of PCMs owing to their superior features such as shape stabilization, enclosure ability, high loading rate, excellent structural stability, and interpenetrating pore morphology. PHPs are monolithic, controllable, highly porous polymers with low density, high specific surface area, highly cross-linked polymer matrix, the porosity of which is created by the continuous phase of emulsions. PHPs in particular stand out for their large gaps bounded by small windows on the skeleton.…”
Section: Introductionmentioning
confidence: 99%